1995
DOI: 10.21273/hortsci.30.5.1009
|View full text |Cite
|
Sign up to set email alerts
|

Far-red at End of Day and Reduced Irradiance Affect Plant Height of Easter and Asiatic Hybrid Lilies

Abstract: Additional index words. Lilium longiflorum, photomorphogenesis, thermomorphogenesis, twilight Abstract. Potted bulbs of Lilium longiflorum Thunb. 'Ace' and 'Nellie White' and Lilium (Asiatic hybrid) 'Enchantment' were grown in a greenhouse under ambient photoperiod (APP), 8-h photoperiod by removing twilight from ambient by blackout cloth (8PP), or 8PP extended with 1 hour of low-intensity far-red radiation (9PP). Height of 'Ace', 'Nellie White', and 'Enchantment' increased by 24%, 18%, and 12%, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…Red/far-red ratio (R/FR ratio) is considered as one of the most important light signals that induce adaptive biochemical and morphological responses known as shade avoidance (Franklin and Whitelam 2005;Franklin 2008). It is wellknown that increasing the fraction of far-red (FR) light causes an increase in internode length and plant height of tobacco (Nicotiana tabacum Burley 21) (Kasperbauer and Peaslee 1973), hybrid lilies (Lilium longiflorum Ace and Nellie White) (Blom et al 1995) and Arabidopsis thaliana (Ruberti et al 2012), which can facilitate light penetration into the plant canopy and consequently can stimulate plant growth and yield of fruit vegetables such as greenhouse tomato. Yang et al (2012) showed increases in leaf area and light interception by supplemental FR light can improve the growth of lettuce (Cucurbita maxima×Cucurbita moschata Tetsukabuto).…”
Section: Introductionmentioning
confidence: 99%
“…Red/far-red ratio (R/FR ratio) is considered as one of the most important light signals that induce adaptive biochemical and morphological responses known as shade avoidance (Franklin and Whitelam 2005;Franklin 2008). It is wellknown that increasing the fraction of far-red (FR) light causes an increase in internode length and plant height of tobacco (Nicotiana tabacum Burley 21) (Kasperbauer and Peaslee 1973), hybrid lilies (Lilium longiflorum Ace and Nellie White) (Blom et al 1995) and Arabidopsis thaliana (Ruberti et al 2012), which can facilitate light penetration into the plant canopy and consequently can stimulate plant growth and yield of fruit vegetables such as greenhouse tomato. Yang et al (2012) showed increases in leaf area and light interception by supplemental FR light can improve the growth of lettuce (Cucurbita maxima×Cucurbita moschata Tetsukabuto).…”
Section: Introductionmentioning
confidence: 99%
“…Red or FR light at the end of the day (photoperiod) is known to affect stem elongation (Blom et al, 1995;Decoteau et al, 1988;Kasperbauer and Peaslee, 1973). Tomato seedlings with end-of-day (EOD) FR light treatment had a greater height and leaf length than those with EOD-R light treatment (Decoteau and Friend, 1991).…”
mentioning
confidence: 99%
“…Height control in lilies can be achieved with several techniques including negative DIF (night temperature greater than day temperature) (Erwin and Heins, 1990), photoperiod control, reduction of far red light (Blom et al, 1995), and chemical plant growth retardants (PGRs) (Lewis and Gilbertz, 1987;Bailey and Miller 1989;Holcomb et al, 1991). The relative ease and flexibility of application make PGRs a popular choice for height control in lilies.…”
mentioning
confidence: 99%